2020
DOI: 10.1371/journal.pone.0216185
|View full text |Cite
|
Sign up to set email alerts
|

Identifying site- and stimulation-specific TMS-evoked EEG potentials using a quantitative cosine similarity metric

Abstract: The ability to interpret transcranial magnetic stimulation (TMS)-evoked electroencephalography (EEG) potentials (TEPs) is limited by artifacts, such as auditory evoked responses produced by discharge of the TMS coil. TEPs generated from direct cortical stimulation should vary in their topographical activity pattern according to stimulation site and differ from responses to sham stimulation. Responses that do not show these effects are likely to be artifactual. In 20 healthy volunteers, we delivered active and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
4
36
0
Order By: Relevance
“…The quality of regression of the realistic sham conditions on early components never significantly differed from noise, as quantified with the classical sham procedure used in the first experiment. This is in line with recent findings suggesting that only late components appear to contain significant PEPs (Biabani et al, ; Freedberg et al, ). In contrast, recruitment curves drawn from active stimulation differed from noise and showed different patterns across sites, possibly revealing different input–output properties of the cortical tissue.…”
Section: Discussionsupporting
confidence: 93%
“…The quality of regression of the realistic sham conditions on early components never significantly differed from noise, as quantified with the classical sham procedure used in the first experiment. This is in line with recent findings suggesting that only late components appear to contain significant PEPs (Biabani et al, ; Freedberg et al, ). In contrast, recruitment curves drawn from active stimulation differed from noise and showed different patterns across sites, possibly revealing different input–output properties of the cortical tissue.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the notion that the N100 is sitespecific and reflects local intracortical excitability-inhibition networks in the targeted brain region. By contrast, other studies found the TMS-evoked N100 to be uniform across several different stimulated brain areas with a stereotypical symmetrical distribution over the vertex irrespective of the targeted cortex region, therefore interpreting it as an unspecific response representing global properties of the brain or even an artifact (Du et al, 2017;Freedberg et al, 2020). In order to use TEPs in neuropsychiatric research and to adequately translate findings into applications as a neurostimulation biomarker, it is crucial to determine which TEP components reflect local cortical properties evoked by direct transcranial effects.…”
Section: Introductionmentioning
confidence: 88%
“…The TEP re ects TMS-evoked brain activation [18][19] that can be speci c to stimulation site [9,12,[20][21][22], and reproducible [12,20,23], particularly at earlier latencies. However, the speci city of longer latency responses is a matter of debate [15,[24][25] due to high correlation between TEPs and sensory responses to TMS by 60-80 ms [16-17,20] and high correlation between active and sham stimulation starting as early as 58 ms [15,17].…”
Section: Introductionmentioning
confidence: 99%